Wireless sensor networks, an energy-aware and utility-based BDI agent approach. (12th April 2007) - Shen, Song; O'Hare, Gregory M.P.
Large-scale wireless sensor applications require that the Wireless Sensor Network (WSN) be sufficiently intelligent to make decisions or tradeoffs within a partially uncertain environment. Such intelligence is difficult to model because the sensor nodes are resource-bounded, especially on energy supply. Within this paper, we model a WSN as a two-level multiagent architecture and introduce the concept of energy-aware and utility-based Belief, Desire, Intention (BDI) agents. We subsequently formalise the fuzzy-set-based belief-generating and theoretically deduce the rules of the meta-level reasoning of a WSN. We further apply a practical reasoning algorithm which enables cost awareness and status awareness within a WSN. A Tileworld-based simulation and subsequent comparison of the effectiveness of bold, cautious and energy-aware and utility-based agents demonstrates that an energy-aware and utility-based BDI agent outperforms other traditional agents, especially when the environment is highly dynamic.